MENINJAU KEMBALI ILMU MAKKI-MADANI (REFLEKSI FILOSOFIS) - Sodikin, Sodikin; Fauzi, Fauzi; Muthalib, Salman Abdul (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2025)
Efforts to study the Qur’an comprehensively have been a strong motivation for Muslim scholars since the early generations and continue to the present day. The various branches of knowledge that support a holistic understanding of the Qur’an have received serious attention and development, including the science of Makki and Madani verses. As a branch of ‘ul?m al-Qur’an, this discipline can be examined through the framework of philosophy of science, which is based on three main branches: ontology, epistemology, and axiology. Ontology relates to one’s understanding of reality, epistemology provides insight into the sources and means of human knowledge, and axiology concerns the values and purposes underlying the relationship between the subject and the object of knowledge. This study finds that although the science of Makki and Madani does not possess a single, definitive definition in theory, this very condition constitutes its uniqueness and undeniable usefulness. Consequently, the study of Makki and Madani verses remains relevant and significant to this day.